2016
DOI: 10.1007/s00277-016-2629-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine restores hematopoietic function by compensating for decreased Tregs in patients with pure red cell aplasia and acquired aplastic anemia

Abstract: Most patients with acquired pure red cell aplasia (PRCA) and some with acquired aplastic anemia (AA) respond well to cyclosporine (CsA), but thereafter often show CsA dependency. The mechanism underlying this dependency remains unknown. We established a reliable method for measuring the regulatory T cell (Treg) count using FoxP3 and Helios expression as markers and determined the balance between Tregs and other helper T cell subsets in 16 PRCA and 29 AA patients. The ratios of interferon-γ-producing CD4 + (Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that Th1 (IFN-γ, TNF-α) is significantly increased with Th2 (IL-4, IL-10) and that Treg cells decrease in an active AS group compared with a normal control group, but this can be reversed after treatment. [11,12] Since cytokines of IFN-γ and TNF-α are hematopoietic negative regulators they can inhibit bone marrow hematopoiesis, which may lead to PRCA. We regret that we did not measure the cytokine level at initial diagnosis, but with the recovery of PRCA and control of AS, the cytokine results showed that the IL-10 level was higher, while TNF-α and IL-4 levels were normal, which indicated a correction with Th1/Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Th1 (IFN-γ, TNF-α) is significantly increased with Th2 (IL-4, IL-10) and that Treg cells decrease in an active AS group compared with a normal control group, but this can be reversed after treatment. [11,12] Since cytokines of IFN-γ and TNF-α are hematopoietic negative regulators they can inhibit bone marrow hematopoiesis, which may lead to PRCA. We regret that we did not measure the cytokine level at initial diagnosis, but with the recovery of PRCA and control of AS, the cytokine results showed that the IL-10 level was higher, while TNF-α and IL-4 levels were normal, which indicated a correction with Th1/Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported that CsA inhibits T cell proliferation and activation, to the best of our knowledge, there is no evidence of CsA inhibiting Tregs in patients with AA. In addition, several previous studies have elucidated that treatment with CsA may increase the number of Tregs in patients with AA and other diseases ( 42 44 ). Previous studies have indicated good efficacy of CsA in the treatment of patients with AA, which may indicate that if it existed, the inhibition of Tregs by CsA may be limited and does not interfere with the treatment effect ( 1 , 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, regulatory T-cells, which maintain self-tolerance and prevent excessive immune activation, have also been found to suppress colony formation in vitro and HSC myeloid differentiation in vivo ( 94 , 95 ). Notably, the numbers of regulatory T-cells are significantly diminished in patients with acquired AA ( 96 ). Specific regulatory T-cell changes following microbial infections in certain system compartments have not been investigated, but may now be detectable with the advent of new cellular subset population analyses ( 97 ).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%